Efektywność metody in-situ w usuwaniu zanieczyszczeń ropopochodnych = Efficiency of removing contamination from the production of petroleum origin by method in-situ - Nguyen, Thi Bich Loc (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The research was carried out in laboratory conditions with the soils which was contaminated with product of petroleum origin. The soil tests were taken from: a railway station (by railway track), air field Przylep (From place to fill up with petrol of plane), petrol station in the street Konstytucja 3-maja in Zielona Góra, Poland. The microbiological studies was analysed in laboratory Institute of Environment Engineering, University of Zielona Góra, Poland in the summer 2010 and 2011of the years.
Keywords: bakterie; ropa naftowa; benzyna; in-situ; bacteria; petroleum; petrol; oil